2005
DOI: 10.1539/joh.47.391
|View full text |Cite
|
Sign up to set email alerts
|

ECG Changes in Humans Exposed to 50 Hz Magnetic Fields

Abstract: ECG Changes in Humans Exposed to 50Hz Magnetic Fields: Srdjan S. BORJANOVIC, et al. Institute of Occupational Health "Dr. Dragomir Karajovic", Serbia and Montenegro-Possible health issues of ELF EMFs include cardiovascular effects since both electrocardiogram and heart-rate changes have been reported in the literature. A non-linear relationship between field strength and biological response has been reported in some studies. In this study, a total of 59 subjects, divided into three independent magnetic field s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
3
8
0
1
Order By: Relevance
“…The most relevant effect, resulting from exposure to combined 50 Hz electric and magnetic fields, is slowing the mean HR (lengthening of the cardiac inter beat interval). This biological effect (Fig 7) was also observed in many studies performed with healthy young men [13], [14], [15] and this response appears attributable to the magnetic aspect of exposure. In our study statistical processing of results (Fig 7), regarding the 50 Hz electromagnetic filed exposure, has an decreasing effect to HR Mean (Student's t-test: Pt=0.001; Mann-Whitney U-test PU=0.003; average difference D=13.2).…”
Section: A Time -Frequency Representationsupporting
confidence: 78%
“…The most relevant effect, resulting from exposure to combined 50 Hz electric and magnetic fields, is slowing the mean HR (lengthening of the cardiac inter beat interval). This biological effect (Fig 7) was also observed in many studies performed with healthy young men [13], [14], [15] and this response appears attributable to the magnetic aspect of exposure. In our study statistical processing of results (Fig 7), regarding the 50 Hz electromagnetic filed exposure, has an decreasing effect to HR Mean (Student's t-test: Pt=0.001; Mann-Whitney U-test PU=0.003; average difference D=13.2).…”
Section: A Time -Frequency Representationsupporting
confidence: 78%
“…Examples from these studies include the ELF-PEMF effect on heart rate variability (HRV) alterations (the low frequency (LF) and high frequency (HF) ratio) [15,16,17], the effect on the 16 Hz/28.3 μT MF exposure to HRV [18], the effect on an intermittent 16.7 Hz MF exposure to heart rate (HR) [19], and the effect on time interval parameters derived from the ECG wave, such as the duration of P and QRS waves, the duration of PR and QT intervals, and corrected QT (QTc) [20]. Graham et al studied specific exposure circumstances under which changes in heart rate variability (HRV) will occur [21].…”
Section: Introductionmentioning
confidence: 99%
“…In a small population cohort of utility workers of 59 substation workers divided into three diVerent exposure categories ("low": 0.067 T; "medium": 1.18 T; "high": 5.2 T), Borjanovic et al found a non-linear response for the cardiac QTc interval: the normalized time between the start of the Q wave and the end of the T wave in the cardiac cycle was shorter in the medium group (Borjanovic et al 2005). Despite these changes, no eVect was found on mean HR or HRV.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…No association between risk of myocardial infarction and elevated workplace EMF exposure Santangelo et al (2005) 28 railway drivers exposed to ELF EMF Exposure not increase the risk of arrhythmias Borjanovic et al (2005) 59 substation workers divided into three diVerent exposure level cohorts…”
Section: Laboratory Studiesmentioning
confidence: 99%